Association between Interlukin-6 (IL-6), Interlukin-10 (IL-10) and depression in patients undergoing Hematopoietic stem cell transplantation - Maria Tavakoli-Ardakani; Maryam Mehrpooya; Mahshid Mehdizadeh; Abbas Hajifathali; Alireza Abdolahi (International Journal of Hematology-Oncology and Stem Cell Research, 2015)
Background: The release of pro-inflammatory cytokines is responsible for the variety of behavioral, neuroendocrine and neuro-chemical alterations in psychiatric condition. In this study we evaluate relation between depression and IL-6 and IL-10 in patients undergoing hematopoietic stem cell transplantation (HSCT). Materials and Methods: 66 patients in this cross-sectional study from July 2013 until August 2014 for HSCT interred the study and were assessed for depression using Hospital Anxiety and Depression Scale (HADS). Serum interleukin (IL)-6, (IL)-10 and high sensitive C-reactive protein (hs-CRP) were assessed on the same time. Association between these biomarkers with depression was evaluated using SPSS version 20. Results: A total of 66 patients with the mean age of 41.18+13.92 and 41.95+12.35 years old in non depressed and depressed group respectively were enrolled in this study. Patients with depression showed significantly higher levels of serum IL-6 and the IL-6-to-IL-10 ratio compared to patients without depression (p<0.001).There was no statistically significant association between IL-10 and hs-CRP with depression in this group of the patients. Conclusions: High IL-6 level has significant association with depression in patients undergoing HSCT. In conclusion, since IL-6 can affect the outcomes after HSCT and depression was associated with increased serum IL-6 level, early identification of depression can be beneficial in these patients.